Statistical Modeling of Migraine Symptom Reduction in Middle-Aged and Elderly Patients: A Comparative Analysis of Aromatherapy Combined with Head Scraping Using Mean and SD Metrics - Nong Jihuan; Huang Renshuai; Liu Qing; Yang Shouyu (BIO Web of Conferences)
Migraine, a prevalent chronic neurovascular disorder, exhibits high incidence rates among middle-aged and elderly populations, with prolonged reliance on conventional Western analgesics often exacerbating comorbidities such as anxiety and depression. To address this challenge, we propose a novel integrative approach combining traditional Chinese medicine (TCM) techniques—aromatherapy and head scraping—with modern statistical modeling to quantify therapeutic efficacy. Through a randomized controlled trial at Wenshan Prefecture Hospital of Traditional Chinese Medicine (with informed consent), migraine patients were stratified into four groups: control (CK), aromatherapy (FX), head scraping (GS), and combined therapy (CK+FX+GS). Symptom reduction was assessed using standardized instruments (MIDAS, HADS, VAS, PSQI), with statistical modeling of clinical outcomes based on mean differences and standard deviation (SD) metrics across groups. The results reveal that the combination therapy group demonstrated significantly lower mean pain intensity (VAS: 0.57 ± 0.75 vs. CK 3.14 ± 0.92, p < 0.01) and psychological well-being (HADS-A: 5.14 ± 1.23 vs. CK 10.71 ± 2.64), PSQI of different groups after treatment are decreased and Grade IV prevalence declined by 73% (p < 0.001), significantly lowering risks of extreme functional impairment. 58% of Grade III patients transitioned to Grade II/I, highlighting broad applicability for moderate disability cohorts in the MIDAS scores. Comparative analysis of SD values further indicated greater consistency in treatment responses within the combination group, suggesting enhanced reliability of the integrated protocol. These results, grounded in descriptive statistical modeling, provide robust evidence for optimizing non-pharmacological migraine management in aging populations while aligning with healthy aging objectives through TCM- Western integrative strategies.